2013
DOI: 10.3928/01477447-20121217-26
|View full text |Cite
|
Sign up to set email alerts
|

Ceramic Liner Fatigue Fracture: 3-D CT Findings in a Late Recurrent THA Dislocation

Abstract: Dislocation is one of the most common complications of total hip arthroplasty (THA). To the authors' knowledge, late recurrent dislocation of a THA with a ceramic-on-ceramic coupling secondary to fatigue fracture of the ceramic liner has never been described. A 76-year-old woman with right hip osteoarthritis underwent cementless modular THA with a ceramic-on-ceramic coupling. Approximately 10 years postoperatively, she experienced right hip pain with no trauma, which resolved in 14 days. Family members reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Frank grinding or crunching sensations are highly concerning; however, other clinical signs such as audible sounds must also be investigated. A creaking or squeaking sound is suggestive of articular malposition and initial failure whereas a duller clicking sound has been suggested to indicate rupture [25], [26]. Any audible sounds can represent a major complication; Malem [27] et al in 2013 report a case in which a patient with a CoC total hip presented with a squeaking hip 5 years post-operatively and was found to have catastrophic failure at revision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Frank grinding or crunching sensations are highly concerning; however, other clinical signs such as audible sounds must also be investigated. A creaking or squeaking sound is suggestive of articular malposition and initial failure whereas a duller clicking sound has been suggested to indicate rupture [25], [26]. Any audible sounds can represent a major complication; Malem [27] et al in 2013 report a case in which a patient with a CoC total hip presented with a squeaking hip 5 years post-operatively and was found to have catastrophic failure at revision.…”
Section: Discussionmentioning
confidence: 99%
“…Any audible sounds can represent a major complication; Malem [27] et al in 2013 report a case in which a patient with a CoC total hip presented with a squeaking hip 5 years post-operatively and was found to have catastrophic failure at revision. Other less specific symptoms include limited range of motion and hip pain [26]. Radiographic analysis can also prove challenging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] However, plain X-ray imaging is not sufficient for delayed acetabular liner fractures since particles might spread until the time of diagnosis. For avoiding misinterpretation and detecting the exact locations of the particles at the hip joint, we need assistance from three-dimensional imaging like CT. Computed tomography scan can be used for early diagnosis at occult ceramic liner fractures, [12] contemporarily to ascertain the presence of ceramic fragments eventually not visible with traditional X-ray. [6] Also, CT can show concomitant bone defects around the implants.…”
Section: Discussionmentioning
confidence: 99%
“…Dale et al showed a 5.3% increase risk of revision due to infection when comparing 1987-1992 to 2003-2007 (30). Second, there can be a failure of other parts of the total hip replacement, i.e., the caput or acetabular component (85,86). When there is a fracture in a ceramic caput component, the taper of the femoral component is at a high risk of damage and therefore necessitates a replacement (Figure 15).…”
Section: Discussionmentioning
confidence: 99%